Komposit Laminate Rami Epoksi Sebagai Bahan Alternatif Socket Prosthesis - Agustinus P. Irawan; Tresna P. Soemardi; Widjajalaksmi K. Widjajalaksmi K.; Agus H.S. Reksoprodjo (Jurnal Teknik Mesin (Sinta 3), 2009)
pure plant oil, biofuel, coconut oil, palm oil, jatropha oilSocket is the most important component in a prosthesis making. Performance criteria for prosthetic socket material include strength, durability, minimal weight, comfort, and minimal fabrication cost. This research attempts to analyze the strength of ramie fiber reinforced epoxy laminate composite as an alternative of socket prosthesis. The research based on ASTM D 3039/D 3039M for tensile strength and ASTM D 695 for compressive strength. The ramie fiber used was a continuous fiber 100 % Ne14'S, with Epoxy Resin Bakelite EPR 174 and Epoxy Hardener V-140. The sample test was created using a hand lay-up method. The result of this research is presented in a correlation of finsile strength (st), compression strength (sc), elasticity modulus (E) versus fraction volume of fiber (Vf). The result is then being compared with some of the prosthesis material’s strength produced by Otto Bock. The analysis was completed with the mode of the failure observation by using Scanning Electron Microscope (SEM). The result concludes that the ramie fiber reinforced epoxy laminate composite is potentially developed further as a socket prosthesis material on Vf 40 – 50 %. Tensile strength and specific strength that has been generated was higher than that of several materias for socket prosthesis, including fiberglass. The mode of the failure found were a brittle failure on Vf: 10-30%, debonding and delamination on Vf: 40-50%. Abstract in Bahasa Indonesia: Socket merupakan bagian terpenting dalam pembuatan prosthesis. Kriteria bahan socket prosthesis antara lain kekuatan, ketahanan, ringan, kenyamanan dan biaya produksi yang rendah. Penelitian ini bertujuan menganalisis kekuatan komposit laminate berpenguat serat rami epoksi sebagai bahan alternatif socket prosthesis. Pengujian kekuatan mengacu standar ASTM D 3039/D 3039M uji tarik dan ASTM D 695 uji tekan. Serat rami yang digunakan berupa serat kontinyu jenis ramie 100 % Ne.14’S dengan matriks Epoxy Resin Bakelite EPR 174 dan Epoxy Hardener V-140. Sampel uji dibuat dengan metode hand lay-up. Hasil pengujian ditampilkan dalam berbentuk hubungan kekuatan tarik (t), tekan (c), modulus elastisitas (E) versus fraksi volume serat (Vf). Hasil pengujian akan dibandingkan dengan kekuatan beberapa bahan prosthesis yang diproduksi oleh Otto Bock. Modus kegagalan diamati dengan bantuan Scanning Electron Microscope (SEM). Berdasarkan pengujian yang telah dilakukan dapat disimpulkan bahwa komposit berpenguat rami epoksi berpotensi untuk dikembangkan sebagai bahan socket prosthesis pada Vf 40–50%. Kekuatan tarik dan spesific strength yang dihasilkan lebih tinggi dari beberapa bahan prosthesis termasuk fiberglass. Modus kegagalan yang terjadi adalah brittle failure (getas) pada Vf : 10-30%, debonding (ikatan lepas) dan delaminasi pada Vf : 40-50%. Kata kunci: Komposit laminate rami epoksi, kekuatan bahan komposit, socket prosthesis.